2014
DOI: 10.1158/1535-7163.mct-13-0870
|View full text |Cite
|
Sign up to set email alerts
|

Antitumor Activity of the Glutaminase Inhibitor CB-839 in Triple-Negative Breast Cancer

Abstract: Glutamine serves as an important source of energy and building blocks for many tumor cells. The first step in glutamine utilization is its conversion to glutamate by the mitochondrial enzyme glutaminase. CB-839 is a potent, selective, and orally bioavailable inhibitor of both splice variants of glutaminase (KGA and GAC). CB-839 had antiproliferative activity in a triple-negative breast cancer (TNBC) cell line, HCC-1806, that was associated with a marked decrease in glutamine consumption, glutamate production, … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

54
896
5
10

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 841 publications
(998 citation statements)
references
References 30 publications
54
896
5
10
Order By: Relevance
“…The Cancer Genome Atlas (TCGA) pan-cancer gene expression data show high expression of GLS in acute myeloid leukemia, adrenocortical cancer, triple-negative breast cancer, colorectal cancer, kidney clear or papillary cell carcinoma, lung adenocarcinoma, melanoma, mesothelioma, pancreatic cancer, sarcoma and thyroid cancer [78,79]. Of these, GLS activity has been shown to be important for growth of acute myeloid leukemia [80][81][82], breast cancer [61,64,83,84], colorectal cancer [85], kidney cancer [86,87], lung cancer [88], melanoma [89,90] and pancreatic cancer cells [91] in studies that utilized smallmolecule inhibitors or gene-silencing approaches in cell lines. Further, glioblastoma cell lines have been found to be sensitive to glutaminase inhibitors in vitro, despite having relatively low GLS expression according to TCGA data [80,92].…”
Section: Kidney-type Glutaminase: Implications In Cancermentioning
confidence: 99%
See 1 more Smart Citation
“…The Cancer Genome Atlas (TCGA) pan-cancer gene expression data show high expression of GLS in acute myeloid leukemia, adrenocortical cancer, triple-negative breast cancer, colorectal cancer, kidney clear or papillary cell carcinoma, lung adenocarcinoma, melanoma, mesothelioma, pancreatic cancer, sarcoma and thyroid cancer [78,79]. Of these, GLS activity has been shown to be important for growth of acute myeloid leukemia [80][81][82], breast cancer [61,64,83,84], colorectal cancer [85], kidney cancer [86,87], lung cancer [88], melanoma [89,90] and pancreatic cancer cells [91] in studies that utilized smallmolecule inhibitors or gene-silencing approaches in cell lines. Further, glioblastoma cell lines have been found to be sensitive to glutaminase inhibitors in vitro, despite having relatively low GLS expression according to TCGA data [80,92].…”
Section: Kidney-type Glutaminase: Implications In Cancermentioning
confidence: 99%
“…The authors also found a variety of terminal substituents that could be tolerated, but did not find any that dramatically improved potency (Figure 7, Shukla_29f). Calithera Biosciences (CA, USA) subsequently described several hundred BPTES derivatives, one of which, CB-839, is currently considered the best-in-class GLS inhibitor, and is undergoing clinical trials for several indications [84,126]. Development of CB-839 expanded upon the studies of Shukla and colleagues, replacing one thiadiazole ring and both phenyl rings, and was the first GLS inhibitor reported to have a low nanomolar potency.…”
Section: Kidney-type Glutaminase: Drug Discoverymentioning
confidence: 99%
“…We then tested the effects of 3 GSL1 inhibitors on the OCR. Compound CB-839 24 and BPTES 27 can inhibit both isoforms, whereas compound 968 is considered to be GAC specific. 8 In OCI-AML2 cells, CB-839, but not BPTES or compound 968, could inhibit the baseline OCR ( Figure 2C).…”
Section: Gac Protein Is Prominently Expressed In Aml and Modulates Thmentioning
confidence: 99%
“…Because drugs are lacking to specifically treat patients with tumors harboring many mutations in genes such KRAS and TP53, one hope is to identify other pathway dependencies in these cancers (16)(17)(18). Both KRAS and TP53 mutations result in metabolic changes, and efforts to target the downstream metabolic effects of these events have demonstrated preclinical potential and led to development of drugs in current clinical trials (19,20). Yet there are also data to suggest that these approaches will not be successful in all KRAS-mutant tumors, raising the possibility that factors other than tumor genetics can contribute to cancer metabolic dependencies (21).…”
Section: Introductionmentioning
confidence: 99%